A high efficient constitutive model of coated plain-weave fabrics under uniaxial tensile loads in arbitrary directions. (21st October 2022) - Sun, Changle; Zhang, Lijuan; Li, Chao
The complex mechanical properties of coated fabrics make it difficult to obtain accurate constants for design and analysis. A high efficient constitutive model of coated plain-weave fabrics is proposed to realize the prediction of mechanical behaviours in arbitrary directions. The coupling mechanism between macro and meso deformation of coated fabrics is analyzed firstly, and the constitutive relation of the model is established based on mesoscopic parameters with clear physical interpretation. Then, the material property values of specimens are obtained by using a multi-objective optimization algorithm according to the experimental data. Unlike the previous constitutive relations which need to use finite element methods to get numerical solutions, the constitutive relation established in this paper can be mapped to a quartic equation with analytical solution, and the calculation efficiency can be greatly improved. The deviations of model predictions with experimental results, e. g., 0.052 (tension), 0.009 (width), 0.014 (length, warp), 0.025 (length, weft), 0.027 (angle, warp), 0.030 (angle, weft), show that the model predictions are in good agreement with the experimental data.